Measles Cases during Ebola Outbreak, West Africa, 2013–2106 - Francesca Colavita; Mirella Biava; Concetta Castilletti; Serena Quartu; Francesco Vairo; Claudia Caglioti; Chiara Agrati; Eleonora Lalle; Licia Bordi; Simone Lanini; Michela Delli Guanti; Rossella Miccio; et al. (Emerging Infectious Diseases, 2017)
The recent Ebola outbreak in West Africa caused breakdowns in public health systems, which might have caused outbreaks of vaccine-preventable diseases. We tested 80 patients admitted to an Ebola treatment center in Freetown, Sierra Leone, for measles. These patients were negative for Ebola virus. Measles virus IgM was detected in 13 (16%) of the patients.